Dignity-based care and infertility treatment: A qualitative study - Zahra Kiani; Masoumeh Simbar; Soheila Nazarpour; Vida Ghasemi (PLoS ONE, 2025)
Introduction The treatment of infertile people is generally time-consuming and requires frequent and long-term visits and providing dignity-based services. Due to the different perceptions and experiences of people and the lack of a specific study to explain the concept of dignity-based care, this study aimed to explain the concept and dimensions of dignity-based care in infertility treatment services. Methods This was a qualitative study with a conventional content analysis approach. Fifty participants (20 infertile women, 16 infertile men, and 14 key informants) were recruited using a purposive sampling method from an educational center of Mazandaran University of Medical Sciences and a private infertility center in Mazandaran –Iran in 2023. Sampling was continued until data saturation. Data were collected using in-depth and semi-structured individual interviews. The data were also analyzed using the conventional content analysis method and the steps suggested by Grandheim and Lundman. Also, Lincoln and Guba’s criteria were used to check the trustworthiness of the data. Results The content analysis demonstrated 43 codes in 11 sub-categories and 4 categories. These categories are “conserving dignity in providing care”, “making the information accessible and obtaining informed consent for care procedure”, “providing professional care and standard services”, and considering cultural and social aspects of infertility. The categories were used to explain the concept and dimensions of dignity-based care in infertility treatment services which are showing the multidimensional aspects of this concept. Conclusion Dignity-based care in infertility treatment services means “conserving dignity in providing care services; making the information accessible and obtaining informed consent for care procedure; providing professional care and standard services; and considering cultural and social aspects of infertility.” This concept can be used in future policy-making and planning, and appropriate support should be taken into account to improve the quality of infertility treatment services.